Ai-enabled Adaptive E-learning Systems Adoption In Conflict Zone: Case Study Of Palestinian Schools - Ashraf Ibrahim Abdallah Qahman; Hadi A. Dahlan; Muhammad Hussin; Murad Ali Ahmad Al-Zaqeba (UIKTEN - Association for Information Communication, 2025)
Indexed Publication (Tier 2)